Research and Practice of "423 Mode" Teaching Based on Scratch Assisted Instruction--Taking the Java Programming Course as an Example - Sheng, Wenwen (Journal of physics. Conference series, 2020)
In the case of a general decline in the quality of students in vocational colleges, how to improve the teaching effectiveness of programming basic courses? This article introduces the use of graphical and Scratch software as teaching aids in the basic courses of higher vocational programming. At this stage, following two lines including Scratch and Java in the course design, and also following "423 model" consists of "pre-class"-"in class"-"after class" in the implementation of the classes to cultivate students' innovative thinking ability, stimulate students' learning interest, reduce the course difficulty and improving course teaching effectiveness. This teaching mode has achieved ideal teaching effect in Java teaching of Rizhao Vocational Technical College.